The integration of Information and Communication Technology for teaching and learning at Ghanaian Colleges of Education: ICT Tutors' Perceptions - John Kwame Eduafo Edumadze (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2016)
ICT is used more at the workplace than in the classroom mainly due to the lack of its extensive integrated into the curriculum by teachers. With the increasing use of ICT in our society, teachers must be at the forefront of it use in order to train their students in its proper use. Ghana's Colleges of Education (COEs) are the first place where ICT education should begin since they are responsible for the training of teachers in the country. The main objective of the study is to evaluate the extent of ICT integration in Ghana's COEs. This study, based on the UNESCO's literature on ICT integration in education and teachers' adoption of ICT, examines the perception of ICT tutors in COEs on the goal to strengthen ICT curriculum in COEs. It also examines their perception of the capability of their students to competently teach ICT studies at the Basic levels in Ghana's education system. Results from the study show that tutors are of the view that ICT integration for teaching and learning are at the beginning stages with respect to Anderson's ICT in Education model. They also are of the view that an elective ICT course should be introduced to train teacher-trainees who will specialise in ICT teaching at our basic level. Finally the study made recommendations to address these challenges.